‫التسيير‬‫المالي‬ ‫في‬ ‫مؤسسات‬ ‫التعليم‬ ‫العالي‬ ‫بين‬ ‫محدودية‬ ‫الا ‫عتمادات‬ ‫المفوضة‬‫ومطلب‬ ‫الجودة‬ ‫في‬ ‫التكوين‬ ‫دراسة‬‫حالة‬ ‫مؤسسة‬ ‫محمد‬ ‫شريف‬ ‫مساعديه‪،‬‬‫سوق‬ ‫أهراس‬ ‫‪-‬‬ - ‫أبوبكر‬ ‫الصديق‫ مهناوي‬‬ (My University, 2018)
This research concerns a sensitive subject, which has recently emerged like the theme of time, you can include because it deals with the financial management of higher education establishments different basic stages and those responsible for these operations, as well as general concepts about the quality of teaching superior in all its elements, without neglecting the scientific research and the extent of its importance in communities, then the level of Algeria in this area compared to countries around the world... this research shows the severity of the impact of a phenomenon which calls for the effect of limited public spending on quality in higher education and research scientist in Algeria… and as a conclusion, the expenses public services cover the main needs of the activity of higher education establishments, but still far from reaching a world quality, moreover, the latest crisis within the government reports that this phenomenon is constantly getting worse... ................................................... يتعلق هذا البحث بموضوع حساس ظهر مؤخراً مثل موضوع الوقت، يمكنك تضمينه لأنه يتعامل مع الإدارة المالية لمؤسسات التعليم العالي المراحل الأساسية المختلفة والمسؤولين عن هذه العمليات، وكذلك المفاهيم العامة حول جودة التدريس متفوقة في جميع عناصرها، دون إهمال البحث العلمي ومدى أهميته في المجتمعات، ثم مقارنة مستوى الجزائر في هذا المجال إلى دول العالم... وهذا البحث يوضح مدى خطورة التأثير لظاهرة تستدعي تأثير محدودية الإنفاق العام حول الجودة في التعليم العالي والبحث عالم في الجزائر... وخلاصة المصاريف الخدمات العامة تغطي الاحتياجات الرئيسية لنشاط مؤسسات التعليم العالي، لكنها لا تزال بعيدة المنال جودة عالمية، علاوة على ذلك، الأزمة الأخيرة داخل وتشير التقارير الحكومية إلى أن هذه الظاهرة تتفاقم باستمرار...